MOLECULAR STRUCTURE AND QUANTUM CHEMICAL CALCULATIONS 4-ETHYL-5-(2-HYDROXYPHENYL)-1,2,4-TRIAZOL-3-THIONE - Satpaeva Zh.B.; Nurkenov O.A.; Turdybekov K.M.; Abulyaissova L.K.; BurkeevM.Zh.; Fazylov S.D.; Talipov S.A.; David Havlicek (Academic Scientific Journal of Chemistry, 2019)
The article is devoted to the study of the spatial structure of 4-ethyl-5-(2-hydroxyphenyl)-1,2,4- triazole-3-thione. The molecular and crystalline structure was determined by x-ray diffraction analysis. Data on the spatial structure and crystal packing of the molecule are presented. It is established that phenyl and triazole rings are flat. Due to hydrogen bonds, the molecules in the crystal form three-dimensional networks. The results of an X-ray diffraction study were deposited at the Cambridge Center for Crystal Structural Data. The structure of the synthesized 1,2,4-triazole was studied by 1H NMR spectroscopy. When analyzing the 1H NMR spectrum of the compound, characteristic signals of the protons of the aromatic ring are observed. The value of the chemical shift and the integrated signal intensity are determined. A quantum chemical study of 4-ethyl-5-(2-hydroxyphenyl)-1,2,4- triazole-3-thione was carried out by the DFT method using the B3LYP exchange-correlation functional in combination with the Danning basic set cc-pVDZ. The molecular characteristics of the compound, such as total electron energy, rotational constants, dipole moment and contributions, and thermodynamic functions, are predicted. The equilibrium geometric parameters of the 4-ethyl-5-(2-hydroxyphenyl)-1,2,4-triazole-3-thione molecule were determined. The performed analysis of the spatial configuration and molecular parameters showed a qualitative correspondence between the crystalline and gas-phase structures of the molecule, while it was noted that the main difference is observed in the relative orientation of six- and five-membered cycles.